The bendabolehbincang Show episode 42. Mitos Kosmologi Nusantara! - Faizal, Mukhtar; Azaini, Manaf (anchor.fm, 2021)
Episode 42: Podcast interview with Dr Ahmad Azaini with his latest book: MITOS Kosmologi Nusantara. Host Faizal Mokhtar discuss on the extract and summarize on the book, and the impact for artists, students and educator alike.